2018
DOI: 10.2224/sbp.7210
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Extroversion and Social Use of Social Networking Sites

Abstract: We investigated a comprehensive model to integrate the negative linear association as well as the positive linear association between extroversion and the social use of social-networking-site behaviors. We examined the possibility of a curvilinear relationship between social use of networking sites and extroversion, revealing U-shaped curvilinear relationships between extroversion and total number of friends, browsing, and leaving comments after controlling for the linear relationship. These findings undersco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Using a variety of personality questionnaires (through which respondents self-report their personality), there is lots of evidence to suggest that behavior on social media is linked to personality traits ( Ong et al, 2017 ). For example, a large body of research has discovered relationships between personality traits and ‘posting’ content ( Ong et al, 2011 ; Bachrach et al, 2012 ; Wang et al, 2012 ; Lee et al, 2014 ; Shen et al, 2015 ; Cheevasuntorn et al, 2017 ; Yoong et al, 2017 ; Casado-Riera and Carbonell, 2018 ; Mo et al, 2018 ; Seidman, 2019 ), ‘liking’ others’ content ( Bachrach et al, 2012 ; Lee et al, 2014 ; Marshall et al, 2015 ; Shchebetenko, 2019 ), and ‘commenting’ ( Gosling et al, 2011 ; Lee et al, 2014 ; Marshall et al, 2015 ; Wang et al, 2018 ). There is therefore a large body of evidence to suggest that relationships exist between traits and social media behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Using a variety of personality questionnaires (through which respondents self-report their personality), there is lots of evidence to suggest that behavior on social media is linked to personality traits ( Ong et al, 2017 ). For example, a large body of research has discovered relationships between personality traits and ‘posting’ content ( Ong et al, 2011 ; Bachrach et al, 2012 ; Wang et al, 2012 ; Lee et al, 2014 ; Shen et al, 2015 ; Cheevasuntorn et al, 2017 ; Yoong et al, 2017 ; Casado-Riera and Carbonell, 2018 ; Mo et al, 2018 ; Seidman, 2019 ), ‘liking’ others’ content ( Bachrach et al, 2012 ; Lee et al, 2014 ; Marshall et al, 2015 ; Shchebetenko, 2019 ), and ‘commenting’ ( Gosling et al, 2011 ; Lee et al, 2014 ; Marshall et al, 2015 ; Wang et al, 2018 ). There is therefore a large body of evidence to suggest that relationships exist between traits and social media behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a recent study takes an integrated look at the parallel of the social compensation hypothesis and social enhancement hypothesis and proposes a U‐curve association between extroversion and online interactions. This non‐linear association was supported by empirical evidence that both introverts and extroverts present active social contacts with others online; however, people with medium levels of extroversion do not manifest frequent socially‐anchored behavior online (Wang, Lv, & Zhang, 2018). Taken together, when investigating dyadic partners’ online interactions from the perspective of extroversion congruence, it is plausible to assume that both extroverted dyads and introverted dyads will have more interactions than dyads with congruent medium levels of extroversion.…”
Section: Introductionmentioning
confidence: 81%
“…Through a review of the literature, this study found that there are still gaps that could be bridged concentrating on the effect of previous cyberbullying victimization experiences on the continuous use of social media, namely the following: (1) there is a debate, mentioned above, over whether previous cyberbullying victimization experiences increases the continuous use of social media or decreases it. One side argues that previous cyberbullying victimization experiences increase the continuous use of social media [ 39 , 40 , 41 ], while the other side argues that they decrease the continuous use of social media [ 42 , 43 ]. (2) Much of the research that investigated the impact of previous cyberbullying victimization experiences on the continuous use of social media was based on linear relationships; however, studies have shown that people’s online behavior does not often follow a constant layer logic, which is to say there may be a nonlinear relationship between previous cyberbullying victimization experiences and the continuous use of social media.…”
Section: Theoretical Frameworkmentioning
confidence: 99%